2021
DOI: 10.2147/jpr.s327945
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Effective Connectivity of the Hippocampus in Migraine without Aura

Abstract: Neuroimaging studies on migraine have revealed structural and functional alterations in the hippocampus, a region involved in pain processing and stress response. This study was designed to investigate whether effective connectivity of this region is disrupted in migraine and relates to chronicity of this disease. Patients and Methods: In 39 episodic migraine (EM) patients, 17 chronic migraine (CM) patients, and 35 healthy controls, we investigated differences in the directional influences between the hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
5
11
0
Order By: Relevance
“…Here, we found that microgliosis, astrogliosis and neuronal loss were present in the cerebral cortex and hippocampus following dural IS stimulation (Fig. 4 ), which may account for the structural and functional alterations in the cerebral cortex and hippocampus of migraine patients previously observed in clinical neuroimaging studies [ 5 , 31 ]. These pathological changes were attenuated by pretreatment with BBG (Figs.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Here, we found that microgliosis, astrogliosis and neuronal loss were present in the cerebral cortex and hippocampus following dural IS stimulation (Fig. 4 ), which may account for the structural and functional alterations in the cerebral cortex and hippocampus of migraine patients previously observed in clinical neuroimaging studies [ 5 , 31 ]. These pathological changes were attenuated by pretreatment with BBG (Figs.…”
Section: Discussionsupporting
confidence: 62%
“…However, the role of P2X7R in migraine-related cognitive impairment has not been disclosed. Migraineurs frequently exhibited structural and functional abnormalities in the cerebral cortex and hippocampus, which is one of the possible mechanisms accounting for cognitive decline in migraineurs [ 5 , 31 ]. In the present study, we observed the elevated expression level of P2X7R in cerebral cortex and hippocampus, brain regions related to cognition, following repeated dural IS stimulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that migraineurs exhibited alterations in the rsFC of amygdala and hippocampus ( Hadjikhani et al, 2013 ; Zhu et al, 2021 ), and the two brain regions were associated with cognition and emotion ( Montagne et al, 2019 ; de Carvalho et al, 2021 ; Dogra et al, 2021 ; Duan et al, 2021 ; Mateus-Pinheiro et al, 2021 ; Nguyen et al, 2021 ). Considering the differences in neuropsychological performance between migraine and TTH ( Waldie et al, 2002 ; Gil-Gouveia et al, 2015 , 2016 ; Huang et al, 2017 ; Puledda et al, 2017 ; Karsan and Goadsby, 2018 ; Vuralli et al, 2018 ), we chose the bilateral amygdala and hippocampus as seed regions for rsFC analyses, to explore the potential rsFC features that may distinguish the two types of headache.…”
Section: Methodsmentioning
confidence: 99%
“…The amygdala and hippocampus are the key brain regions related to cognition and emotion ( Montagne et al, 2019 ; de Carvalho et al, 2021 ; Dogra et al, 2021 ; Duan et al, 2021 ; Mateus-Pinheiro et al, 2021 ; Nguyen et al, 2021 ). The alterations in rsFC of the two brain regions have been reported in migraineurs when compared to healthy controls (HCs) ( Hadjikhani et al, 2013 ; Zhu et al, 2021 ). However, there is a lack of studies to directly compare functional brain connectivity between migraine and TTH.…”
Section: Introductionmentioning
confidence: 99%